MELACAK JEJAK IMPLEMENTASI PENGEMBANGAN ENERGI ALTERNATIF DI PEDESAAN: STUDI KASUS TENTANG PENGEMBANGAN BIOETANOL BERBASIS SINGKONG DI JAWA BARAT - Anugrah Saputra (Jurnal Renaissance, 2018)
This study discusses the intervention of government policy through the policy of biofuels (BBN) based on cassava in rural areas. The government program intended to build an independent village by introducing renewable energy with a bioethanol energy program in the village by bring new knowledge and perspective to the local community about renewable energy issues. The struggle against the meaning and practice of alternative energy continues to roll in line with the various interests that color at the local level. This research was conducted using qualitative method with explorative descriptive format and conducted to reach description of adaptation to the implementation of alternative energy program in rural area. This research through data collected with interviews and document analysis. The research findings the government driven bioethanol programs are the sectoral ministry of ESDM, without involving other related institutions. Cassava-based alternative energy has not been able to encourage the progress of the village, due to the unchanged behavior of the community on cassava, land issues for cassava, technological constraints, and socio-economic conditions of bioethanol that are not formed. This results that program does not sustainable in the future .Keywords: bioethanol, adaptation and strategy, sustainability